no ragrets - Elangovan, Nivani (Nanyang Technological University, 2023)
A skeleton on a skateboard or a fat pigeon farting — why would anyone get these quirky and ‘doodle’-looking scribbles on their skin forever? A daring new-age tattoo style has been steadily growing popular globally these past few years, and is starting to make a wave in Singapore. no ragrets is a light-hearted, raw and purposefully haphazard 15-minute documentary seeking to understand why youth are so smitten with these nonsensical or ‘ignorant’ tattoos.